Work-life balance and conflict in retail company: Tesco Stores (Malaysia) Sdn Bhd / Khairol Izwan Harry - Harry, Khairol Izwan (Faculty of Business and Management, 2013)
The need to reconcile working with non-working life (family and domestic responsibilities) has been gaining importance over the decades, as a result of increasing female employment rates in Malaysia and drastic changes in family patterns, changes that have given rise to a growing number of nuclear or single-parent families. Studies in the area of work-life balance have so far mainly concentrated on the conflict between people’s work and other life roles. It is generally accepted that there is a clear link between work-life conflict and work-life balance, as attaining work-life balance is dependent on managing or reducing the conflict between various roles.